Formation of Social Bonds in School on the Basis of Gender, Ethnic, and Social Delimitation - Vorlíček, Radek (Lidé města, 2024)
Through the observation of educational settings, this article raises issues concerning the social status of Roma children in the context of schooling. The article deals with social distance dynamics among pupils in elementary school, and its impact on their position in the social hierarchy. It is based on long-term qualitative fieldwork. The central method of the fieldwork was observation. The results draw attention to many aspects of social exclusion in educational settings.